PENERAPAN MEDIA PERMAINAN KARTU KATA DAN RODA KEBERUNTUNGAN MENINGKATKAN PENGUASAAN KOSAKATA BAHASA MANDARIN SISWA KELAS X - Mulyatik, Mulyatik; Thamrin, Lily; Veronica, Tjen (Universitas Tanjungpura, 2024)
The purpose of this study was to understand the use of word card and wheel of fortune game media for teaching Mandarin Vocabulary, it aimed to analyze the advantages and disadvantages of word card and wheel of fortune game media in teaching Mandarin Vocabulary. This research utilized an experimental research method. Data collection methods were in the form of student response questionnaires and written test (Pretest and Posttest). The study